Integrating Islamic Podcasts to Enhance Student Engagement in Islamic Religious Education Learning - M. Ramli; Cantik Tri Rahajeng; Hannan Wayeh (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
The digital transformation of Islamic education has intensified the need for learning media that are not only technologically accessible but also pedagogically meaningful and aligned with Islamic values. At the Madrasah Aliyah level, sustaining students’ engagement in Islamic Religious Education (PAI) remains a persistent challenge, particularly within online and hybrid learning settings. Addressing this issue, the present study aims to examine the integration of Islamic podcasts into PAI learning and to explore their contribution to students’ learning interest, participation, conceptual understanding, and independent learning practices. This study employed a qualitative multiple-case study design in three State Madrasah Aliyah in Banjarmasin, involving students, PAI teachers, and madrasah administrators as research participants. Data were collected through participant observation, in-depth interviews, and document analysis over one academic semester and were analyzed thematically using the Miles, Huberman, and Saldaña framework. The findings demonstrate that integrating Islamic podcasts enhanced students’ engagement in learning by encouraging more active participation, deeper conceptual understanding, and more meaningful involvement in classroom discussions. Podcasts also improved access to learning, enabled flexible, repeated access to instructional materials, and fostered stronger independent learning habits among students. In addition, the narrative and contextual nature of podcast-based learning supported students’ emotional and spiritual connection with Islamic values. The originality of this study lies in its contextual and pedagogical contribution to Islamic education by positioning Islamic podcasts not merely as digital tools, but as integrative learning media that connect cognitive, affective, and spiritual dimensions within the madrasah context.